Pengaruh Corporate Governance Terhadap Kinerja Keuangan Perusahaan Perbankan Yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2019 - Annisa Annisa (Jurnal Ilmiah Pendidikan Scholastic, 2020)
The purpose of this research was to determine the effect of corporate governance on the performance of banking companies listed on the Indonesia Stock Exchange. The number of samples examined in this study were as many as 31 companies using the period from 2015 to 2019 so that the number of samples studied were 115 samples. Based on multiple linear regression tests conducted where each increase in managerial ownership will reduce financial performance. Based on multiple linear regression tests conducted where each increase in institutional ownership will improve financial performance. The results of the study are based on the t-test carried out for managerial ownership variables where the conclusions obtained are managerial ownership which has a negative and significant effect on financial performance. Based on the t test conducted for institutional ownership variables in which the conclusion obtained is institutional ownership has a positive and significant effect on financial performance. Based on the simultaneous F test, it was concluded that managerial ownership and institutional ownership variables have a joint or overall effect on financial performance. The amount of ability of independent variables in explaining the dependent variable is 14.3%, while the remaining 85.7% can be explained by other variables outside of the research model or research variables.